M2 macrophage polarization in systemic sclerosis fibrosis: pathogenic mechanisms and therapeutic effects - Mingyue Hu; Zhongliu Yao; Li Xu; Muzi Peng; Guiming Deng; Liang Liu; Xueyu Jiang; Xiong Cai (Heliyon, 2023)
Systemic sclerosis (SSc, scleroderma), is an autoimmune rheumatic disease characterized by fibrosis of the skin and internal organs, and vasculopathy. Preventing fibrosis by targeting aberrant immune cells that drive extracellular matrix (ECM) over-deposition is a promising therapeutic strategy for SSc. Previous research suggests that M2 macrophages play an essential part in the fibrotic process of SSc. Targeted modulation of molecules that influence M2 macrophage polarization, or M2 macrophages, may hinder the progression of fibrosis. Here, in an effort to offer fresh perspectives on the management of scleroderma and fibrotic diseases, we review the molecular mechanisms underlying the regulation of M2 macrophage polarization in SSc-related organ fibrosis, potential inhibitors targeting M2 macrophages, and the mechanisms by which M2 macrophages participate in fibrosis.